2020
DOI: 10.1038/s41467-020-16327-0
|View full text |Cite
|
Sign up to set email alerts
|

An integrated multi-omics approach identifies the landscape of interferon-α-mediated responses of human pancreatic beta cells

Abstract: Interferon-α (IFNα), a type I interferon, is expressed in the islets of type 1 diabetic individuals, and its expression and signaling are regulated by T1D genetic risk variants and viral infections associated with T1D. We presently characterize human beta cell responses to IFNα by combining ATAC-seq, RNA-seq and proteomics assays. The initial response to IFNα is characterized by chromatin remodeling, followed by changes in transcriptional and translational regulation. IFNα induces changes in alternative splici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(180 citation statements)
references
References 84 publications
11
155
0
Order By: Relevance
“…In line with this concept, type I IFN is expressed in human islets from donors with T1D, 1 and children genetically at risk for the disease present a type I IFN transcriptomic signature in the circulation before the development of autoantibodies 2 . In addition, laser‐captured islets obtained from living donors with recent‐onset T1D show a significant increase in the expression of IFN‐stimulated genes 3 and human islets exposed in vitro to IFNα or to interleukin‐1β (IL‐1β) + IFNγ have gene signatures that are similar to those observed in islets obtained from patients affected by T1D, but not by type 2 diabetes 4,5 . We recently found that exposure of human beta cells to IFNα induces three hallmarks of human T1D, namely, release of chemokines, endoplasmic reticulum (ER) stress and a massive human leukocyte antigen (HLA) class I overexpression.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In line with this concept, type I IFN is expressed in human islets from donors with T1D, 1 and children genetically at risk for the disease present a type I IFN transcriptomic signature in the circulation before the development of autoantibodies 2 . In addition, laser‐captured islets obtained from living donors with recent‐onset T1D show a significant increase in the expression of IFN‐stimulated genes 3 and human islets exposed in vitro to IFNα or to interleukin‐1β (IL‐1β) + IFNγ have gene signatures that are similar to those observed in islets obtained from patients affected by T1D, but not by type 2 diabetes 4,5 . We recently found that exposure of human beta cells to IFNα induces three hallmarks of human T1D, namely, release of chemokines, endoplasmic reticulum (ER) stress and a massive human leukocyte antigen (HLA) class I overexpression.…”
Section: Introductionmentioning
confidence: 75%
“…In children at risk of developing T1D, a type I IFN transcriptional signature is detected ahead of seroconversion for autoantibodies, suggesting that activation of the innate type I IFN pathway occurs very early in the development of the disease 2 . Furthermore, islets obtained from patients affected by T1D show a gene signature similar to human islets treated in vitro with pro‐inflammatory cytokines 4,5 . It remains to be proven by clinical trials, however, whether and/or to what extent INFα is a key cytokine for the induction of insulitis and the autoimmune killing of beta cells in T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA of EndoC-βH1 cells and of pancreatic human islets exposed or not to IFNα or to IL-1β + IFNγ for the indicated time points was obtained and prepared for RNA sequencing as described (3234). Bioanalyzer System 2100 (Agilent Technologies, Wokingham, UK) was used to evaluate samples quality by determining RNA integrity number (RIN) values.…”
Section: Methodsmentioning
confidence: 99%
“…There are also marked inter-individual differences in BCM independently of disease [ 13 , 22 , 31 ], and BCM mass in people with T2D has substantial overlap with BCM of non-diabetic individuals and patients with impaired glucose tolerance [ 32 ]. Finally, beta cell dysfunction(s) and the pro-inflammatory environment in T1D or the metabolic stress in T2D lead to considerable changes in gene expression profile [ 14 , 33 , 34 , 35 , 36 ], which complicates the identification of a biomarker suitable for beta cell quantification across disease states. Therefore, the ideal probe/target should be exquisitely beta cell-specific and sensitive enough to allow discrimination between healthy individuals and diabetic patients without being affected by beta cell stress secondary to disease pathogenesis.…”
Section: Beta Cell Imaging Is a Cornerstone For Future Individualimentioning
confidence: 99%
“…Our group has approached the discovery of novel beta cell biomarkers by combining two proposed complementary approaches, namely, using human islets or beta cells from the start and focusing on the identification of specific splice variants present in human beta cells, but not in other human tissues [ 34 , 35 , 45 , 99 , 100 ]. Our present approach for biomarker discovery is shown in Figure 1 .…”
Section: New Experimental Approaches To Identify Beta Cell Biomarkmentioning
confidence: 99%